Stomach versus heart: case report of a giant hiatal hernia with perforated gastric ulcer with obstructive shock - Sanchez, Yankel A.; Ayub, Omar Z. (International Journal of Research in Medical Sciences, 2022)
A giant paraesophageal hernia is defined when at least 30% of the stomach has moved to the thorax or the presence of another intra-abdominal organ. We describe the presentation of a clinical case of a giant hiatal hernia with perforated gastric ulcer in a 52-year-old man who presented to the emergency department with pain in the inguinal region developing obstructive shock. Presentation of hiatal hernias is usually asymptomatic and in some cases with atypical signs and symptoms involving cardiovascular and respiratory disorders. In patients with a history of gastroesophageal reflux disease/ with atypical thoracic symptoms, hiatal hernia and its complications should be ruled out.